CODE SWITCHING AND CODE MIXING IN TOURISM INDUSTRY TOWARD MULTILINGUAL - samsi, yogi setia (Script Journal: Journal of Linguistic and English Teaching, 2016)
Asian Economics Community ( MEA )Â  hasÂ  bigÂ  influence for everyone in the world. This agreement will attract more and more people from other countries to come, stay dan work in Indonesia. Therefore, people need to communicate with more than one language in multilingual culture. This study is sociolinguistic which aimed to find out the form of code switching and code mixing are used by people, to know the purpose and influence of code switching and code mixing that found in tourism industry of Karawang toward daily conversation. The data are taken from Delonix Hotel in Karawang by using observation and interview of Japanese, English, Indonesia, and Sundanese people which analyzed about code switching and code mixing as holmesâs theory (2013). Data interpretation provides that the form of code switching and code mixing are occurred in their conversation in Delonix Hotel in Karawang. The result of interpretation shows that code switching and code mixing is determined by social, cultural, and individual factors.